How Do Speakers Define the Meaning of Expressions? The Case of German x heißt y ("x means y"). Issue 3 (15th March 2020) - Helmer, Henrike
ABSTRACT: To secure mutual understanding in interaction, speakers sometimes explain or negotiate expressions. Adopting a conversation analytic and interaction linguistic approach, I examine how participants explain which kinds of expressions in different sequential environments, using the format x heißt y ("x means y"). When speakers use it to clarify technical terms or foreign words that are unfamiliar to co-participants, they often provide a situationally anchored definition that however is rather context-free and therefore transferable to future situations. When they explain common (but indexical, ambiguous, polysemous, or problematic) expressions instead, speakers always design their explanation strongly connected to the local context, building on situational circumstances. I argue that x heißt y definitions in interaction do not meet the requirements of scientific or philosophical definitions but that this is irrelevant for the situational exigencies speakers face.